1977
DOI: 10.1152/ajpcell.1977.233.1.c1
|View full text |Cite
|
Sign up to set email alerts
|

Rate of heat production related to degree of filament overlap in chick ALD muscle

Abstract: The anterior latissimus dorsi (ALD) of chicks (2 wk old) was examined for rate of heat liberation when the muscle was reversibly stretched from L0 to about 1.6 L0. The "plateau" forces of isometric tetani were related to the corresponding rates of heat liberation. Presumably, in this region of length change the degree of overlap between the thick and thin filaments is changing. If the amount of overlap is known, the number of heavy meromyosin cross bridges in activity can be estimated. From this information, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Others have found that the P = 0 intercept of heat versus tension is a substantial fraction of the total maintenance heat in experiments where the full range of tension was examined (e.g. Smith, 1972, on striated muscle from Rana temporaria and Bufo bufo, and Matsumoto & McPhedran, 1977, on chick striated muscle).…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that the P = 0 intercept of heat versus tension is a substantial fraction of the total maintenance heat in experiments where the full range of tension was examined (e.g. Smith, 1972, on striated muscle from Rana temporaria and Bufo bufo, and Matsumoto & McPhedran, 1977, on chick striated muscle).…”
Section: Discussionmentioning
confidence: 99%